Adult Learners and Short-term Study Abroad: Formation or Transformation? - John M. Dirkx; Robert Spohr; Laura Tepper; Susan Tons (Adult Education Research Conference, 2010)
This paper reports on the identity work in which adult learners engage who are participating in a graduate, short-term, study-abroad program in higher and adult education.